2020
DOI: 10.1167/iovs.61.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Choriocapillaris Impairment in ABCA4 Maculopathy Is Secondary to Retinal Pigment Epithelium Atrophy

Abstract: To analyze the progression of choriocapillaris (CC) impairment in recessive Stargardt disease (STGD) and compare it to the progression of retinal pigment epithelium (RPE) atrophy. METHODS. Fifty-five patients with a clinical diagnosis of STGD and genetic confirmation of pathogenic biallelic variants in ABCA4 were imaged with short-wavelength fundus autofluorescence (SW-AF) and optical coherence tomography angiography (OCTA) at a single clinic visit, whereas a subset of 12 patients were imaged with the same mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Furthermore, in a previous study from our group, we observed more significant atrophy of the choriocapillaris as detected by OCT angiography in patients with chorioretinal atrophy compared to patients with discrete atrophy. 32 Despite the difference in disease severity between these two phenotypes, however, we observed a similar rate of lesion enlargement between the two groups, suggesting that the process of RPE atrophy is similar amongst different STGD1 phenotypes.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, in a previous study from our group, we observed more significant atrophy of the choriocapillaris as detected by OCT angiography in patients with chorioretinal atrophy compared to patients with discrete atrophy. 32 Despite the difference in disease severity between these two phenotypes, however, we observed a similar rate of lesion enlargement between the two groups, suggesting that the process of RPE atrophy is similar amongst different STGD1 phenotypes.…”
Section: Discussionmentioning
confidence: 49%
“…They also found a dark halo of the lesion perimetry, probably corresponding to a shadow cast by lipofuscin accumulation in the RPE overlying the CC. These results demonstrate the advantage of using OCTA imaging in monitoring disease, and the authors concluded that as the RPE becomes atrophic, the CC disappears as a downstream effect [ 12 ].…”
Section: Optical Coherence Tomography Angiography and Spectral Domain...mentioning
confidence: 83%
“…The near-infrared autofluorescence (NIR-AF) signal originates from melanin in the RPE and the choroid. It has been thought that NIR-AF can better delineate the degree of RPE atrophy [ 12 ] ( Figure 1 and Figure 2 ). The full-field electroretinogram is usually normal or minimally abnormal, whereas multifocal electroretinogram (mf-ERG) may show a more demonstrable reduction of central retina responses [ 6 ].…”
Section: Fundus Autofluorescence and Near Infrared Autofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…This evidence suggests that RPE atrophy occurs first, then followed by CC atrophy, as previously described in ABCA4-related conditions. 20 The study suffers from several limitations mainly related with the "case report design" of the investigation.…”
Section: Discussionmentioning
confidence: 99%